»Retterbuch« und Richterbuch - Pfeiffer, Henrik 1964- (2015)
Abstract: In a critical reflection upon the article of S. Golani (»Three Oppressors and Four Saviors – The Three-Four Pattern and the List of Saviors in I Sam 12,9–11«, ZAW 127/2 [2015]) this study discusses problems in the hypothesis of a pre-Dtr ›Judges Composition‹ as an earlier stage of the book of Judges.
Zusammenfassung: Der Beitrag diskutiert in kritischer Reflexion des Aufsatzes von S. Golani »Three Oppressors and Four Saviors – The Three-Four Pattern and the List of Saviors in I Sam 12,9–11« (ZAW 127, Heft 2-2015) Probleme der Hypothese einer vor-dtr. Richterkomposition als Vorstufe des Richterbuches.
Résumé: L’article traite des problèmes liés à la postulation d’une étape préliminaire du livre des Juges sous forme d’une composition pré-dtr, à partir d’une discussion critique de l’article de S. Golani »Three Oppressors and Four Saviors – The Three-Four Pattern and the List of Saviors in I Sam 12,9–11« (ZAW 127, 2-2015).